Anti-feminisms in media culture - White, Michele; Negra, Diane 1966- (Routledge, Taylor & Francis Group, 2022)
"This important and timely collection examines the troubling proliferation of anti-feminist language and concepts in contemporary media culture. Edited by Michele White and Diane Negra, these curated essays offer a critical means of considering how contemporary media, politics and digital culture function, especially in relation to how they simultaneously construct and displace feminist politics, women's bodies, and the rights of women and other disenfranchised subjects. The collection explores the simplification and disparagement of feminist histories and ongoing feminist engagements, the consolidation of all feminisms into a static and rigid structure, and tactics that are designed to disparage women and feminists as a means of further displacing disenfranchised people's identities and rights. The book also highlights how it is becoming more imperative to consider how anti-feminisms, including hostilities towards feminist activism and theories, are amplified in times of political and social unrest and used to instigate violence against women, people of color, and LGBTQIA+ individuals. A must read for students and scholars of media, culture and communication studies, gender studies, and critical race studies, with an interest in feminist media studies"--